Effects of intravenous dexmedetomidine on spinal anesthesia and sedation - A comparison of two different maintenance infusions - Pritee H Bhirud; Shrividya Chellam; Mandar N Mote; Pratibha V Toal (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: Our aim was to study the effects of a low-dose bolus (0.5 mcg/kg) of dexmedetomidine followed by two different infusion doses (0.25, 0.5 mcg/kg/h) on spinal anesthesia, sedation, hemodynamics and side effects. Material and Methods: Eighty consenting patients were randomized into two groups A and B with 40 patients each. Patients in both groups were administered intravenous (IV) dexmedetomidine 0.5 mcg/kg over 10 min prior to SAB followed by IV dexmedetomidine 0.25 mcg/kg/h infusion (A) and 0.5 mcg/kg/h infusion (B) throughout the duration of surgery. Time for onset of sensory and motor block, duration of motor block and analgesia, time for two segment regression, intra operative hemodynamics and sedation were assessed. P value less than 0.05 was taken as significant. Results: Onset of sensory block to T10 was 2.1 ± 0.3 min in group A and group B. Onset of motor block was 4.6 ± 0.9 min in group A and 4.3 ± 0.9 min in group B. Duration of motor block in group A was 235.6 ± 12.4 min compared to group B which was 245.3 ± 9.3 min. Time for 2 segment regression in group A was 139.7 ± 29.7 min compared to group B which was 152.3 ± 18.7 min. Total duration of analgesia was 259.3 ± 92.4 min in group A and 273.8 ± 52.3 min in group B. There was a significant reduction in heart rate and mean blood pressure compared to the baseline within both the groups. Sedation was comparable in both the groups. Conclusion: IV dexmedetomidine bolus of 0.5 mcg/kg prior to subarachnoid block followed by maintenance infusion of 0.5 mcg/kg/h significantly prolonged duration of motor block, time for two segment regression, along with stable hemodynamics and adequate sedation.